Synergic impact of beekeeping on crop production and income in Chambal region of Madhya Pradesh - Singh, Y P; Yadav, Ravi S; Yadav, Ashok S; Singh, Sudhir (Indian Farming, 2020)
Bee keeping, a non-land based income generating agribusiness, is emerging as an important component for integrated rural development and off-farm employment. Observations revealed that the extraction of honey varied from 6 to 64 kg/ha from flowering period of crops, fruit and forest plants. The maximum honey extract came from mustard crop (64 kg/ha) followed by coriander (40 kg/ha) and least with sesame crop (6 kg/ha). The honey bees as pollinators increased the yield of crops by 3.3-31.2% compared to the yield without bee keeping fields. Among various crops, the additional income from honey was maximum (` 6,400/ha) with mustard and lowest (` 660/ha) with sesame. Like-wise, overall (yield of honey and crops) maximum additional income ` 21,900/ ha was obtained from mustard and least with sesame (` 8,260/ha). Bee keeping is a low investment and high income generating business. Bee keeping also provides employment to rural people and arrest migration towards cities, besides enhancing income and employment for businessmen and manufacturers of bee keeping rearing equipments.